ETHICAL SUFISM IN IMAM AL-GHAZALI'S IHYA ULUM AL-DIN: ITS RELEVANCE TO ISLAMIC RELIGIOUS EDUCATION - Muhammad Nuzhan; Khalilurrahman Khalilurrahman (STIT Darul Hijrah Martapura, 2026)
This study aims to examine the concept of ethical Sufism developed by Imam Al-Ghazali in Ihya Ulum al-Din and its relevance to Islamic Religious Education (IRE. It is driven by the growing phenomenon of moral decline and character deterioration among students, highlighting the urgent need to reinforce character education grounded in spiritual values. The research adopts a qualitative approach through library research, focusing on Al-Ghazali’s works especially Ihya Ulumuddin as well as other relevant supporting literature. The results indicate that Al-Ghazali’s ethical Sufism centers on the purification of the soul (tazkiyat al-nafs), self-discipline, consistent practice of virtuous actions, and the development of the heart as the core of moral consciousness. These principles are highly applicable to the advancement of Islamic Religious Education, particularly in fostering students’ character through the internalization of values, the exemplary role of teachers, and the cultivation of spiritual habits. Accordingly, Al-Ghazali’s ethical Sufism can be positioned as a foundational framework for strengthening moral education in contemporary Islamic Religious Education.